Parasite trading model using neuro-fuzzy system - Ng, Wei Jie (2016)
The popular use of program trading in current financial market, had gained a lot of attention by the public. However, the rule-based approached often determined by experience traders, does not fully utilized the capability of computerized trading. Not only so, many of the neuro-fuzzy architecture implemented for financial application is focusing on Time-Series Price Prediction.